Changes in Basel capital requirements and lending ability of African commercial banks - Damilola Oyetade; Adefemi Alamu Obalade; Paul-Francois Muzindutsi (Journal of Central Banking Theory and Practice, 2022)
This research examines the potential impact of Basel IV capital requirements (CAR) on bank lending ability in Africa. To achieve the objective, the study simulated Basel IV capital ratio using historical data to create sample representative banks as if the selected banks had implemented Basel IV CAR for the period 2000 and 2018 and used actual data for existing Basel II and III CAR. Dynamic panel regression analyses, namely the System GMM and P-ARDL, were utilised. First, our results suggest that higher Basel CAR, particularly the new Basel IV, portends short-term negative impacts on bank lending while the long-term impact on bank lending is favorable. Second, the weight of non-performing loans tends to decline as banks transitioned from lower to higher Basel CAR. Lastly, this study shows that complying with Basel IV CAR will help African banks to achieve financial deepening and increase bank lending ability.
Keywords: G18; G21; G28; 330; African Banks; Bank lending; Basel capital requirements; risk assessment